2007
DOI: 10.1051/forest:2006092
|View full text |Cite
|
Sign up to set email alerts
|

Divergence among species and populations of Mediterranean pines in biomass allocation of seedlings grown under two watering regimes

Abstract: -Seedlings of four populations each of Pinus pinaster, P. halepensis, P. canariensis and P. pinea were grown in controlled conditions to evaluate both inter-and intra-specific differences in response to watering. We submitted half of the plants to a moderate water stress and after 22 weeks, we recorded height, stem diameter and root, stem and leaves dry weight. Patterns and amounts of phenotypic changes, including changes in biomass allocation, were analysed. We found a scant response in P. canariensis, P. pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
92
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 48 publications
9
92
0
7
Order By: Relevance
“…The lack of population × year interaction is in accordance with Danjon (1994) who found a stable ranking of the P. pinaster populations for height across years. The absence of a population × site interaction agrees with Chambel et al (2007) who found a non significant population × treatment interaction in P. pinaster seedlings in response to drought stress.…”
Section: Growthsupporting
confidence: 78%
“…The lack of population × year interaction is in accordance with Danjon (1994) who found a stable ranking of the P. pinaster populations for height across years. The absence of a population × site interaction agrees with Chambel et al (2007) who found a non significant population × treatment interaction in P. pinaster seedlings in response to drought stress.…”
Section: Growthsupporting
confidence: 78%
“…(i) Differences in phenotypic plasticity among populations, representing an adaptive response to environmental heterogeneity resulting from biotic or abiotic factors. Phenotypic plasticity is under genetic control, has been reported in Maritime pine provenances (Chambel et al, 2007), and was present at the across and within-site level in our study. Population differences in phenotypic plasticity, associated to divergent trends in populations from similar environments, may explain the apparently non-congruent macroenvironments for total height (Fig.…”
Section: Ge Interactionsupporting
confidence: 51%
“…A high level of phenotypic plasticity for growth and drought tolerance has been reported in several studies (Chambel, 2007;Hopkins and Butcher, 1993;Zas et al, 2004), with Atlantic provenances displaying lower survival under severe water deficits (Alía et al, 1995) or frost stress (Hopkins and Butcher, 1993). Differences in stem form have also been found among populations, mainly explained by differences in competition for light and resistance to snow and wind, with highland populations displaying a better form (González-Martínez et al, 2002;Sierra de Grado et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The number of dwarf shoots was also reduced by drought. The occurrence of dwarf shoots in pine seedlings is a sign of maturity which can be used to evaluate the ontogenetic stage of the seedling (Chambel et al, 2007). Thus, the results from both seedlings' growth and number of dwarf shoots, taken together, suggest that water deficit reduces carbon gain and slows down ontogenetic development in this, like in many other species.…”
Section: Impact Of Water Deficit On the Studied Traits: Intraspecificmentioning
confidence: 99%